Modelagem e simulação de sistema logístico de distribuição de carne de frango - Siqueira, Álvaro José Herzog (2014)
The logistics system for distribution of finished products is characterized by the integration of communication, transport and financial services in order to meet the demands of consumers. It is estimated that in Espírito Santo state, the per capita consumption of poultry meat is 44.4 kg per year. To meet this demand, the state has slaughter plants distributed throughout its territory and, count with other companies in the country. In transport systems, vehicle routing problem (VRP) are characteristic, which need to be studied, characterized and optimized, usually through computer routines for permitting to access greater number of variables. This study aimed to characterize a VRP of a slaughter plant in South Region of Espírito Santo state, and to develop a computer program that supports logistic managers, serving to evaluate existing and proposed routes, and to analyze logistic parameters of a product distribution process. In the development of computer application was necessary to characterize the logistics system of the company, collect and analyze data of logistic operations, develop computational algorithms that represent the system under study, verify and validate the computer application, and then perform experiments. The developed application allowed represents data of the studied system and evaluate routes second logistic parameters. Thus, according to this study, can be concluded that the developed computer program is useful designed for logistic managers, for enabling the evaluation of the existing routes and new routing settings.